A fragment of an unknown Armenian homiletic collection from the Georgian National Centre of Manuscripts - Dali Chitunashvili (Banber Arevelagitut'yan Instituti)
In the Armenian manuscripts fund of the Georgian National Centre of Manuscripts there is preserved a Gospel, which paleographically dates back to the 15th century [10:238]. The Gospel was restored in the 60s of the 20th century, and the fragments of the authentic leather cover are preserved. In the course of the restoration, it appears that two sheets of parchment used as flyleaves have been removed. The parchment fragments are horizontally cut parts of a single sheet and attract attention from both paleographical and textual perspectives. Before being cut, the size of the fragment was 320x210, but even this does not reflect the original size of the parchment sheet, since only one column survives in the fragment, that too incompletely, and the manuscript must have been written in at least two columns. In the fragment preserved today, the size of the column is 115 mm, the distance be-tween the columns is 20 mm, there are 22 lines in the column, the distance between the lines is 10 mm, the bottom margin is 110 mm, and the right margin is 82 mm.